Keputusan pembelian produk fashion di Shopee: Analisis peran live streaming dan user-generated content (UGC) - Sarip, Sarip Maulana; Savitri, Citra; Pramudita Faddila, Syifa (Journal of Management and Digital Business, 2026)
The purpose of this study is to analyze the influence of live streaming and user-generated content (UGC) on Shopee users’ fashion product purchase decisions. This study employs a quantitative causal-associative approach. Data were collected via an online questionnaire from 130 Shopee users who had been exposed to live streaming and UGC features; the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that, individually, live streaming and user-generated content have a significant influence on fashion product purchase decisions on Shopee. These findings confirm that consumer purchasing decisions are influenced by interactive content features and live streaming that provide product education. The conclusion of this study indicates that live streaming and UGC serve as supporting information channels, but have not yet become dominant factors in determining fashion product purchasing decisions. Therefore, sellers are advised not to rely solely on live streaming and UGC, but to combine them with other strategies. Further research is recommended to include additional variables or to compare with other e-commerce platforms to yield broader, more in-depth results.